Enlarged blepharoplasty: treating the upper two-thirds of the face - Armando Chiari; Sergio Antonio Saldanha Rodrigues-Filho (Revista Brasileira de Cirurgia Plástica)
Introduction: Patients may show signs of facial aging still in the early stages of life when complex surgical procedures are not sought, especially if they result in larger scars. These signals should be detected and treated appropriately for effective rejuvenation. Methods: In the last 23 years,338 patients have undergone upper blepharoplasty associated with transpalpebral elevation of the eyebrows and myectomies of corrugators. They also received a mid-facial facelift through a lower blepharoplasty incision, with a detachment of the retaining orbital ligaments and repositioning an extensive flap of the orbicularis muscle in the superolateral direction. Canthopexy was routinely performed. Results: Simultaneous rejuvenation of the upper two-thirds of the face is performed through simple blepharoplasty incisions, and this systematization is not found in the current literature. Patients were satisfied with the results, and routine canthopexy effectively prevented lower eyelid positioning defects. The most common complications were temporary paraesthesia (frontal and scalp regions) and chemosis in the lateral and lower aspects of the conjunctiva. In a retrospective review of 139 procedures performed between 2010 and 2019, the temporary scleral show was observed in 15 cases (10.8%) and a mild ectropion in 1 case (0.72%), treated conservatively. Two cases of chemosis (1.44%) and one hematoma (0.72%) required surgical treatment. Conclusion: Enlarged blepharoplasty is safe, allows direct vision of manipulated periorbital structures, does not require long or expensive instrumental training. The authors achieve aesthetic results that impress by the rejuvenation of the upper 2/3 of the face and the lasting effect.